A comparative study to evaluate the vitamin D status in rheumatoid arthritis patients - Ram Ranjan Singh; Md Abu Nasar; Brajesh Kumar Singh; Khursheed Alam (International Journal of Health and Clinical Research, 2021)
Introduction: Vitamin D deficiency has been shown to be associated with autoimmune diseases, which is a controversial finding in various previous studies. Moreover there are limited studies done on serum vitamin D and its association with rheumatoid arthritis in Indian population. Aim: The present study was designed to study the level of vitamin D in patients with rheumatoid arthritis and to compare it with healthy controls. Materials and Methods: The study included 40 patients diagnosed for rheumatoid arthritis (RA) and 40 age and sex matched healthy controls who were willing to participate in the study. After obtaining the written informed consent from all the participants, 2 ml of blood was collected in a plain vacutainer for the estimation of vitamin D by chemi-luminescent method.Results: The cut off values of 25-OH vitamin D level, being <20ng/ml as deficiency, 29 -30ng/ml as insufficiency and >30ng/ml as normal. There was neither any statistical difference in the vitamin D levels nor in the vitamin D deficiency level (<20ng/ml) between the two groups (p= 0.302), 82.5% of the patients with RA had Vitamin D deficiency and 80% of the controls had vitamin D deficiency.Conclusion: As vitamin D levels are significantly low in the healthy general population, this could be the reason for no association of vitamin D deficiency and rheumatoid arthritis.